On Zagreb Indices of Two New Operations of Graphs - Bharali, A.; Buragohain, J.; Mahanta, A. (Communications in Mathematics and Applications, 2019)
Recently, Wang et al. (2017) introduced two new operations of graphs. In this paper we establish explicit expressions of some Zagreb indices viz. first Zagreb index, second Zagreb index and forgotten topological index of these two newly proposed operations of graphs. Then as an application we further establish explicit formulae of some other topological indices of the two operations of graphs.